1985
DOI: 10.1002/jhrc.1240081113
|View full text |Cite
|
Sign up to set email alerts
|

Automatic simulated distillation of heavy petroleum fractions up to 800°C TBP by capillary gas chromatography. Part I: Possibilities and limits of the method

Abstract: The characterization of heavy petroleum fractions is essential for the design and improvement of cracking plants converting heavy feedstock into valuable "white" products. Conventional simulated distillation methods using packed columns are unsuitablefor this purposes, being limited to boiling points up to about 600OC. The method presented is able to cover a boiling points interval ranging from about 150°C up to around 800OC. It employs a short, nonpolar, highly thermostable capillary column routinely operated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 5 publications
1
17
0
2
Order By: Relevance
“…As primeiras publicações sobre o assunto surgiram no final da década de 70 e início da de 80 29,34,35 . São basicamente três os métodos utilizados para a compensação de linha de base a partir da análise em branco 29,35 : subtração ponto a ponto de uma linha de base armazenada; subtração ponto a ponto após zerar matematicamente a linha de base inicial com a armazenada e reconstrução de uma linha de base armazenada, de forma que os pontos do início e do final sejam os mesmos do cromatograma da amostra.…”
Section: Fundamentosunclassified
“…As primeiras publicações sobre o assunto surgiram no final da década de 70 e início da de 80 29,34,35 . São basicamente três os métodos utilizados para a compensação de linha de base a partir da análise em branco 29,35 : subtração ponto a ponto de uma linha de base armazenada; subtração ponto a ponto após zerar matematicamente a linha de base inicial com a armazenada e reconstrução de uma linha de base armazenada, de forma que os pontos do início e do final sejam os mesmos do cromatograma da amostra.…”
Section: Fundamentosunclassified
“…L'arrivée ces dernières années de colonnes métalliques très stables et l'utilisation de régulateurs électroniques de pression et débit a permis de mieux maîtriser ces paramètres [55,56]. Ces progrès ont aussi permis de repousser le point final d'ébullition déterminé jusqu'à 720 °C, avec l'apparition de la distillation simulée haute température (DSHT) [57]. La gamme de point d'ébullition des produits pétroliers est ainsi pratiquement couverte, mais en utilisant deux méthodes puisque la DSHT ne peut travailler qu'avec des coupes de point d'ébullition supérieur à 150 °C.…”
Section: Distillation Simuléeunclassified
“…In the first report [!3l aC-90alkane was noted to emerge from the column at 390OC. In the second and more extensive study [6], n-alkanes containing up to 100-1 10 carbon atoms were eluted during temperature programming of the column up to 430°C.Afinal isotherm of about 30 minutes at 43093 extended the range to C-130 to Following Sandra's detailed investigation [ 11, we also observed that certain specially prepared [7] selective methyl and methyl phenyl polysiloxanes when coated onto polyimide clad fused silica capillary columns could readily maintain their film stability at 370% Because of our long experience with the surfaces of fused silica glass considering the many advantages ofthis type of glass when compared to borosilicate glass, we were of the opinion that a new type of high temperature capillary column with outstanding characteristics could be fabricated hereonce the temperature limitation of the polyimide outer coat was overcome. A study was carried out in an attempt to achieve this goal.…”
Section: Introductionmentioning
confidence: 98%
“…The "Dexsil" series of silicone-carborane polymers, so popular for the analysis of high molecular weight materials by gas chromatography using packed columns at temperatures up to 350-450°C plus, do not wet well on the surface Recently, Luke and Ray [5], and Trestianu and his colleagues [6], described the use of short (less than 15 meters) borosilicate glass capillary columns coated with methyl polysiloxane, a nonpolar stationary phase, for the separation of high molecular weight hydrocarbons at high temperatures. In the first report [!3l aC-90alkane was noted to emerge from the column at 390OC.…”
Section: Introductionmentioning
confidence: 99%